Intensified microwave-assisted hydrodistillation produces Trans-Anethole-Rich Fennel (Foeniculum vulgare Mill.) fruit essential oil - Ilić Dušica P.; Troter Dragan Z.; Stanojević Jelena S.; Cvetković Dragan J.; Ristić Ivan S. (Chemical Industry and Chemical Engineering Quarterly)
Fennel fruit (Foeniculim vulgare Mill.) essential oil (FFEO) was isolated from disintegrated plant material by intensified microwave-assisted hydrodistillation approach (MWHD). Isolated FFEO, rich in trans-anethole and low in estragol, was obtained with a 30% higher yield after only 10 min compared to the FFEOs isolated via traditional hydrodistillation (HD). Besides significant differences in the chemical composition, the MWHD-obtained FFEO demonstrated superior antibacterial activity, while its anticandidal activity remained unchanged and identical to HD-obtained FFEOs. MWHD technique also required almost 18 times less electricity consumption and emitted less CO2 than the conventional HD, suggesting this approach is more viable for FFEO production on an industrial level. According to these results, the MWHD-obtained FFEO has the potential to be used in the food industry and packaging, for the production of nutraceuticals, biopharmaceuticals, bioherbicides, and cosmetics.